Perilaku Mengemudi dan Pengalaman Wisatawan: Sebuah Studi di Kawasan Metropolitan Bandung - R. Rina Novianty Ariawaty; Layyinaturrobaniyah Layyinaturrobaniyah; Egi Arvian Firmansyah; Hilmiana Hilmiana; Kurniawan Saefullah (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
Driving behavior significantly influences tourist comfort and experiences in a destination, making traffic management a critical consideration for tourism-focused cities. This study examines driving behaviors in Bandung and assesses their impact on tourists' comfort and overall experiences. A total of 300 respondents, consisting equally of drivers and tourists, participated through an online questionnaire administered via Google Forms across West Bandung Regency, Bandung Regency, Cimahi City, and selected areas of Sumedang Regency in West Java Province, a method particularly effective during the COVID-19 pandemic. Descriptive statistical analysis and independent t-tests indicate that driving behavior among Bandung residents is moderately deviant; however, most drivers tend to comply with traffic regulations and consider receiving telephone calls while driving as relatively unimportant. Nevertheless, tourists emphasize enhancing public transportation services and traffic orderliness. The study confirms a significant relationship between driving behavior and tourist experiences, highlighting the need for targeted improvements to develop Bandung as a more comfortable and attractive city for residents and visitors.